Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To find the ratio [tex]\( e : g \)[/tex] given the following ratios:
[tex]\[ e : f = 4 : 3 \][/tex]
[tex]\[ f : g = 5 : 6 \][/tex]
we need to link these two ratios together by the common term [tex]\( f \)[/tex].
### Step-by-Step Solution:
1. Convert the given ratios into fractional form:
From [tex]\( e : f = 4 : 3 \)[/tex]:
[tex]\[ \frac{e}{f} = \frac{4}{3} \][/tex]
From [tex]\( f : g = 5 : 6 \)[/tex]:
[tex]\[ \frac{f}{g} = \frac{5}{6} \][/tex]
2. Combine the two ratios by eliminating the common term [tex]\( f \)[/tex]:
We need [tex]\( \frac{e}{g} \)[/tex]. To combine these, let's first express [tex]\( f \)[/tex] in terms of a common measure:
From [tex]\( e : f = 4 : 3 \)[/tex]:
[tex]\[ e = \frac{4}{3} f \][/tex]
From [tex]\( f : g = 5 : 6 \)[/tex]:
[tex]\[ f = \frac{5}{6} g \][/tex]
3. Substitute the expression for [tex]\( f \)[/tex] from the second ratio into the first ratio:
Using [tex]\( f = \frac{5}{6} g \)[/tex] in [tex]\( e = \frac{4}{3} f \)[/tex]:
[tex]\[ e = \frac{4}{3} \left( \frac{5}{6} g \right) \][/tex]
Simplify the fraction:
[tex]\[ e = \frac{4 \cdot 5}{3 \cdot 6} g \][/tex]
[tex]\[ e = \frac{20}{18} g \][/tex]
4. Simplify the ratio [tex]\( \frac{20}{18} \)[/tex]:
The greatest common divisor (GCD) of 20 and 18 is 2. To simplify:
[tex]\[ \frac{e}{g} = \frac{20}{18} = \frac{20 \div 2}{18 \div 2} = \frac{10}{9} \][/tex]
5. Express the simplified ratio [tex]\( e : g \)[/tex]:
[tex]\[ e : g = 10 : 9 \][/tex]
### Answer:
[tex]\[ e : g = 10 : 9 \][/tex]
[tex]\[ e : f = 4 : 3 \][/tex]
[tex]\[ f : g = 5 : 6 \][/tex]
we need to link these two ratios together by the common term [tex]\( f \)[/tex].
### Step-by-Step Solution:
1. Convert the given ratios into fractional form:
From [tex]\( e : f = 4 : 3 \)[/tex]:
[tex]\[ \frac{e}{f} = \frac{4}{3} \][/tex]
From [tex]\( f : g = 5 : 6 \)[/tex]:
[tex]\[ \frac{f}{g} = \frac{5}{6} \][/tex]
2. Combine the two ratios by eliminating the common term [tex]\( f \)[/tex]:
We need [tex]\( \frac{e}{g} \)[/tex]. To combine these, let's first express [tex]\( f \)[/tex] in terms of a common measure:
From [tex]\( e : f = 4 : 3 \)[/tex]:
[tex]\[ e = \frac{4}{3} f \][/tex]
From [tex]\( f : g = 5 : 6 \)[/tex]:
[tex]\[ f = \frac{5}{6} g \][/tex]
3. Substitute the expression for [tex]\( f \)[/tex] from the second ratio into the first ratio:
Using [tex]\( f = \frac{5}{6} g \)[/tex] in [tex]\( e = \frac{4}{3} f \)[/tex]:
[tex]\[ e = \frac{4}{3} \left( \frac{5}{6} g \right) \][/tex]
Simplify the fraction:
[tex]\[ e = \frac{4 \cdot 5}{3 \cdot 6} g \][/tex]
[tex]\[ e = \frac{20}{18} g \][/tex]
4. Simplify the ratio [tex]\( \frac{20}{18} \)[/tex]:
The greatest common divisor (GCD) of 20 and 18 is 2. To simplify:
[tex]\[ \frac{e}{g} = \frac{20}{18} = \frac{20 \div 2}{18 \div 2} = \frac{10}{9} \][/tex]
5. Express the simplified ratio [tex]\( e : g \)[/tex]:
[tex]\[ e : g = 10 : 9 \][/tex]
### Answer:
[tex]\[ e : g = 10 : 9 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.